PENGARUH PENGANGGARAN, TRANSPARANSI KEBIJAKAN PUBLIK DAN AKUNTABILITAS PUBLIK TERHADAP PENGAWASAN KEUANGAN DAERAH (Survei Pada Kantor Dewan Perwakilan Rakyat Daerah Provinsi Sulawesi Tengah) - Sabaria, Nini; Totanan, Chalarce; Jamaluddin, Jamaluddin (Katalogis, 2018)
This research aims at examining and analyzing The Effect of Budgeting, Transparency of Public Policy and Public Accountability on Regional Financial Supervision (Survey at The Office of The People’s Representative council in Central Sulawesi Province), either simultaneously or partially. The method used is saturated or census sampling. The respondents of this study amounted to 39 members of the people’s representative council in the province of central Sulawesi who were sampled. The technique of Data collection was survey technique by distributing questionnaires. The analytical toll used is multiple linear regression analysis with the help of Statistical Package for Social Science (SPSS). The results of this study indicate that the Budgeting, Transparency of Public Policy and Public Accountability on Regional Financial Supervision simultaneously contributes positive and significant influence Regional Financial Supervision. While partially Budgeting, Transparency of Public Policy and Public Accountability exccution contributes positive and significant influence Regional Financial Supervision at The Office of The People’s Representative council in Central Sulawesi Province.